ANALISIS PERSEPSI GURU TERHADAP KONSEP PENERAPAN MERDEKA BELAJAR DI SD INPRES ANTANG I KOTA MAKASSAR: . - Junaeda, Junaeda; Khalik , Muh. Fihris; Fitri, Riskal (ALENA : Journal of Elementary Education, 2023)
This study aims to determine teachers' perceptions of the concept of implementing independent learning and the factors that support and inhibit the implementation of independent learning at SD Inpres Antang I, Makassar City. The method used is qualitative and data collection techniques used are observation, interviews and documentation. Based on the results of research on teacher perceptions of the concept of implementing independent learning at SD Inpres Antang I, Makassar City. Shows that teachers at SD Inpres Antang I, Makassar City, have a positive perception and get a very good appreciation of the Free Learning curriculum, by implementing independent learning students will be able to improve their abilities because they are given freedom in the learning process. The research results also explain the importance of socialization massively to all parties at the education unit level, so that the implementation of the curriculum can be implemented properly as expected. Apart from that, teachers' perceptions at SD Inpres Antang I have several indicators in implementing the independent learning curriculum, including: teachers' perceptions of the new curriculum, cancellation of national exams, simplification of lesson plans, and also PPDB Zoning System, and factors that support the implementation of independent learning are teachers , parents, principals and students, then what becomes a factor in inhibiting the implementation of independent learning is the management of learning time.